THE RELATIONSHIP BETWEEN HEIGHT AND SHOOTING ACCURACY OF PETANQUE ATHLETES AT GUNUNG LEUSER UNIVERSITY ACEH - Rio Sahputra; Afrizal; Husaini (CV Naskah Aceh, 2025)
The purpose of this study was to determine the relationship between height and shooting accuracy in the sport of petanque at Petanque University Gunung Leuser Aceh.The purpose of this study was to determine the relationship between height and shooting accuracy in the sport of petanque at Petanque University Gunung Leuser Aceh. The population in this study were those who had participated in the Regional Student Sports Week (POMDA) of petanque sports and researchers used the total sampling theory of the entire population as a sample. The instrument used to determine height is the stadiomete / meter test. Meanwhile, to measure shooting accuracy using the shooting game station. From hypothesis testing the results obtained, height has a relationship with shooting accuracy in petanque sports in petanque athletes at Gunung Leuser University Aceh, where the correlation coefficient (rxy) = 0.45> rtab value ɑ (0.05 = 0.444) with a coefficient of determination = 0.20 or 20%. Based on data analysis, it can be concluded that there is a significant relationship between height and shooting accuracy in petanque sports in petanque athletes at Gunung Leuser University Aceh.